Circular motion: A learning experience to improve understanding of circular motion. - Orellana Contreras, Carlos Enrique; Llugsa Llambo, Anthony Ariel; Varguillas Carmona, Carmen Siavil (Revista Minerva, 2025)
This article implements a practical and demonstrable laboratory equipment that, together with concrete materials, interactive activities and exercises, facilitates the understanding, analysis and application of the principles of Uniform Circular Motion (MCU). By connecting theory and practice, it fosters meaningful learning that promotes a critical and comprehensive vision of this physical concept, in addition to developing analytical skills in students. The present study aims to analyze the perception of students about the effectiveness of a laboratory equipment designed to facilitate learning using an entitative approach with a descriptive scope, using as a data collection technique the survey; Likert scale with a sample of 15 fifth semester students of the 2024-1S period of the pedagogy of experimental sciences Mathematics and Physics of the UNACH The results show a positive perception of the students towards the methodology based on the experimental equipment designed to teach Uniform Circular Motion (MCU). With an average of 4.47 out of 5 in the perception of the material as appropriate to understand the subject, and 4.60 in the link between theory and practical applications, its effectiveness is highlighted. These findings, aligned with the theories of Domínguez (2015) and Dewey (1938) on the value of practical experience, reflect not only an improvement in learning, but also in the motivation of students, promoting their recommendation for future uses in abstract physics topics. Concluding that the laboratory equipment was fundamental to facilitate the understanding of complex physics concepts.